Computed tomographic (CT) arthrogram contributes to the diagnosis of an osteochondroma of the distal calcaneus in a horse. (9th April 2020) - de Souza, T.; Jones, R.; Foote, A.; Suthers, J.
Summary: Osteochondromas in the horse are most commonly found as a solitary lesion affecting the distal radial metaphysis. In this location, diagnosis is reliant on radiographic and ultrasonographic examination and confirmed with post‐operative histopathology. This case report describes the additional benefit of performing a CT arthrogram to aid the diagnosis of an osteochondroma in an atypical location.